Victorian servants, class, and the politics of literacy - Fernandez, Jean, 1956- (Routledge studies in nineteenth-century literature, 2010)
Utilizing an array of cultural texts, fiction, servant autobiography, diaries and pamphlets, this study examines the debate on mass literacy as it developed around the figure of the Victorian servant, as well as its significance for understanding the nexus between class and narrative power in nineteenth-century literature.